Labour and capitalist transformation in Asia: report on a conference - Kannan, K.P.; Rutten, Mario (2002)
Just as the labour movement and trade unions have been unable to keep up with the recent changes at a global level, most studies on labour and capitalist transformation continue to operate within old debates, views and perspectives and are hardly able to take into their approach and analysis the changes due to the recent acceleration in the process of globalisation. An attempt to address this concern by bringing back labour into the research agenda. - Reproduced.
Keywords: Labour